Knowledge about tobacco smoking among medical students in Saudi Arabia: Findings from three medical schools - Hoda Jradi; Ali Al-Shehri (Springer, 2019)
Introduction: Tobacco smoking is the leading cause of preventable death worldwide. Educating and training medical students about tobacco dependence prevention and treatment will prepare them for the task of helping smokers quit. In Saudi Arabia, little is known about medical students' knowledge on this topic. Methods: This study was conducted among 237 medical students (89% response rate) from three medical schools in Saudi Arabia. Students were asked to complete a 55-item questionnaire about the knowledge of smoking epidemiology, smoking cessation practice and benefits, and treatment of tobacco dependence. Results: The majority of the students (91.4%) do not have adequate knowledge about the epidemiology of smoking. Students demonstrated a low knowledge of the health risks associated with tobacco use (average score 53%; SD = 11.6), a fair understanding of the benefits of smoking cessation, and insufficient information about treatment of tobacco dependence. Respondents thought they were adequately prepared to counsel their patients to quit smoking. Conclusions: Medical students in Saudi Arabia are not well informed and trained in tobacco dependence and treatment. It is necessary to address this deficit by prioritizing these topics in medical education curricula.